An experimental evaluation of engine performance and emissions characteristics of a modified direct injection diesel engine operated in RCCI mode - Tien Duy Nguyen; Trung Tran Anh; Vinh Tran Quang; Huy Bui Nhat; Vinh Nguyen Duy (AIMS Energy, 2020)
This study explored methods to evaluate the test engine characteristics operated based on the reactivity controlled compression ignition (RCCI) technology to reduce fuel consumption and exhaust emissions, especially PM and NOx. Consequently, gasoline and diesel, respectively, considered as the low reactivity fuel (LRF) and high reactivity fuel (HRF), are injected in the intake manifold and combustion chamber. The experimental procedure is conducted at a constant speed of 2000 rpm, and brake mean effective pressure (BMEP) from low load 0.84 bar to high load 4.24 bar. The injection strategy is varied according to the engine loads. Indeed, at the low and medium engine load condition, the diesel fuel is injected double injection pulse, at the high load, the diesel fuel is injected single injection pulse. The injection timing is advanced from the top dead center (TDC) until knocking happens or the coefficient of variation (COV) higher than 10%, and maximum advanced injection timing is 65 crank angle degree (℃A) before the top dead center (BTDC). The results of advanced injection timing show that limit of advanced timing in low load is COV while at high load is knocking; at medium load, the diesel injection timing can be advanced to 65℃A BTDC. The exhaust emissions of CO and HC are higher than conventional diesel engines, while soot is hugely lower in all operating points. NOx emission is much dependent on injection timing, at 10 to 20℃A BTDC NOx highest, and approximately to the conventional diesel engine, NOx reduction when injection timing advanced.